2017
DOI: 10.1007/s00262-017-2043-6
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 blockade alters the tumor microenvironment and augments the response to cancer immunotherapy in a mouse model

Abstract: Recent findings show that immune cells constitute a large fraction of the tumor microenvironment and that they modulate tumor progression. Clinical data indicate that chronic inflammation is present at tumor sites and that IL-4, in particular, is upregulated. Thus, we tested whether IL-4 neutralization would affect tumor immunity. Current results demonstrate that the administration of a neutralizing antibody against IL-4 enhances anti-tumor immunity and delays tumor progression. IL-4 blockade also alters infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…Studies revealed that IL-4 antibody neutralization enhances anti-tumor immunity and delays tumor progression. IL-4 blockade also alters in ammation in the tumor microenvironment, reducing the generation of both immunosuppressive M2 macrophages and myeloid-derived suppressor cells, and enhancing tumorspeci c cytotoxic T lymphocytes [24]. In our study, we found that FPR2 played an auxo-action on secretion of IL-10 and IL-4 in ovarian cancer cells, and induction of M2 macrophages polarization.…”
Section: Macrophages Play An Indispensable Role In Defensing Against supporting
confidence: 54%
“…Studies revealed that IL-4 antibody neutralization enhances anti-tumor immunity and delays tumor progression. IL-4 blockade also alters in ammation in the tumor microenvironment, reducing the generation of both immunosuppressive M2 macrophages and myeloid-derived suppressor cells, and enhancing tumorspeci c cytotoxic T lymphocytes [24]. In our study, we found that FPR2 played an auxo-action on secretion of IL-10 and IL-4 in ovarian cancer cells, and induction of M2 macrophages polarization.…”
Section: Macrophages Play An Indispensable Role In Defensing Against supporting
confidence: 54%
“…If Th2 responses are elicited in consequence of alternatively activated macrophages in the tumor tissue, it promotes the formation of an immunosuppressive microenvironment as shown in patients with esophageal cancer [ 133 ]. This was a central issue in a recent study by Ito et al, showing that blocking IL-4 changes the microenvironment of the tumor to the favor of Th1-polarization from Th2 in mice, suggesting a possible enhancement of human immunotherapy by IL-4 mAb treatment [ 134 ]. Pharmacologic interventions can also have a significant effect on Th17 responses in mouse models [ 135 ].…”
Section: T Helper Cell Polarization Direct and Indirect Mechanisms Omentioning
confidence: 99%
“…These results also indicate that IFN-g and IL-4 play an antagonistic role in the differentiation of TAMs and that targeting IL-4 in the TME may contribute to lung cancer treatment. Indeed, it has been found that targeting the elevated IL-4 in the TME also alters inflammation in the tumor microenvironment, reducing the generation of immunosuppressive M2 macrophages and myeloid-derived suppressor cells (MDSCs), which enhances anti-tumor immunity and delays tumor progression (41). Moreover, tumor-derived CSF-1 and IL-4 synergistically induce M2-type polarization of macrophages (42).…”
Section: Interleukins and Chemokinesmentioning
confidence: 99%